Retained Embolized Fragment of Totally Implantable Central Venous Catheter in Right Ventricle: It is Really Necessary to Remove?. Issue 5 (September 2015) - Tazzioli, Giovanni; Gargaglia, Eleonora; Vecchioni, Ilaria; Papi, Simona; Di Blasio, Petronilla; Rossi, Rosario
Introduction: Central venous catheters are often required in oncologic patients for long-term safe administration of chemotherapeutic agents, antibiotics, and parenteral nutrition. Rupture of these devices and intracardiac migration is a rare complication. Methods: We report one spontaneous rupture and embolization of a totally implantable vascular access device (TIVAD) in an asymptomatic patient. Results: A 50-year-old woman received a TIVAD silicone catheter 8 FR for adjuvant chemotherapy. After 3 years of port time in situ, during a follow-up control, a catheter malfunction was found and radiologic investigations showed a rupture and migration of the catheter to the right ventricle. The attempt to remove the fragment under fluoroscopic control using the femoral route was unsuccessful. We did not try a surgical approach because of the complete absence of symptomatology and hemodynamic impairment. Conclusions: The catheter rupture and intracardiac embolization is a rare complication associated with totally implantable or tunneled central venous catheters. When such an event happens, the patient should be managed by expert hemodynamists or interventional radiologists making an effort to remove the fragment without surgical measures. When the intravascular percutaneous route fails, the possibility to leave the fragmented catheter in heart chambers should be evaluated, being surgery questionable in asymptomatic patients.